Uncovering Brazilian Otiocerinae (Hemiptera: Fulgoromorpha: Derbidae): description of three new species and first records for the tribes Sikaianini Muir, 1913 and Patarini Emeljanov, 1995 - Bitar, Murilo Victor Silva; Domahovski, Alexandre Cruz (Zootaxa, 2025)
Despite the subfamily Otiocerinae being the largest in Derbidae by a great margin, there was only one recorded species in Brazil to date. A survey conducted by the authors at the Coleção Entomológica Padre Jesus Santiago Moure of the Universidade Federal do Paraná (UFPR) revealed a considerable number of undescribed Brazilian otiocerines, as well as other derbid species. Here, we describe three new species of Brazilian Otiocerinae: Mula flamma sp. nov., from Mato Grosso State; Otiocerus shamshir sp. nov., from Paraná State; and Patara paladinae sp. nov., from states of Paraná and Santa Catarina. Each species belongs to a different subtribe: Sikaianini Muir, 1913, Otiocerini Muir, 1917, and Patarini Emeljanov, 1995, respectively. The wing venations are described in detail, and hypotheses regarding vein identity are discussed.